Melatonin inhibits oxidative stress and apoptosis in fetal brains of hyperhomocysteinemic rat dams - Baydas, Giyasettin; Koz, Sema T.; Tuzcu, Mehmet; Etem, Ebru; Nedzvetsky, Viktor S. (Wiley, 2007)
Moderate hyperhomocysteinemia is a risk factor for neurodegenerative diseases and complications during pregnancy. Increased homocysteine levels during pregnancy may elevate developmental risk on fetal brain structure and function. However, little is known about the mechanism of action of homocysteine on the degeneration of the fetal brain. Hence in this study, we examined the effects of maternal hyperhomocysteinemia on oxidative stress and apoptosis in brain tissues and investigated whether administration of melatonin to the mother would prevent homocysteine-induced oxidative cerebral damage in pups. Hyperhomocysteinemia was induced in female rats by administration of methionine at a dose of 1 g/kg body weight dissolved in drinking water during pregnancy. Some animals received methionine plus 10 mg/kg/day melatonin subcutaneously throughout pregnancy. After delivery, the level of lipid peroxidation (malondialdehyde + 4-hydroxyalkenals) was determined in different subfractions of pup brains. Furthermore, DNA fragmentation, levels of Bcl-2 protein and p53 mRNA expression were determined to evaluate apoptosis. Significant elevation was found in the levels of lipid peroxidation in subcellular fractions of the brain of pups of hyperhomocysteinemic dams. Increased DNA fragmentation and p53 mRNA expression was observed in the brain of pups of homocysteine-treated rats, while a significant reduction was seen in the levels of anti-apoptotic Bcl-2 levels. Melatonin administration prevented markers of oxidative stress and biochemical signs of apoptosis. In conclusion, therapeutic administration of melatonin protects against the induction of oxidative stress and neural tissue injury and might prevent congenital malformations of fetal brain caused by maternal hyperhomocysteinemia.
Keywords: apoptosis; hyperhomocysteinemia; melatonin; oxidative stress; pup brain